Structure and field evolution of magnetic skyrmions in Co/Pt-based multilayers by in-situ electron holography - Andersen, Ingrid Marie (2023)
Room-temperature stable skyrmions are interesting candidates for future spintronic technology. A thorough understanding of their characteristics and the ability to manipulate these topological spin structures is crucial for their application in devices. Co/Pt-based multilayer systems offer a tunable platform to study magnetic skyrmions at room temperature [1]. However, there is an experimental challenge in resolving magnetic structures in such multilayer stacks with few stack repetitions approaching the ultrathin (1 nm) limit